1984
DOI: 10.1192/bjp.144.4.376
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Recognition-Memory and Hedonic Tone a Signal Detection Analysis

Abstract: A signal detection analysis was used in a recognition memory task involving material of varying hedonic tone. Major differences were found between the control and depressed states. Although overall recognition rates were the same, pleasant material was recognised less and unpleasant material more easily by depressives. Neutral material was recognised equally well by both groups. In the depressed state, response biases were altered such that unpleasant material was handled in a preferential way to neutral or pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
1
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 34 publications
8
74
1
1
Order By: Relevance
“…This finding is entirely consistent with the results of studies of long-term memory for emotional events, which have shown that emotions improve the memories of events and of some of their properties (e.g., location) (e.g., D'Argembeau & Van der Linden, 2004;Dunbar & Lishman, 1984). Therefore, contrary to findings in the literature on time distortions in long-term memory for emotional events, our results suggest that durations are remembered better when they are initially experienced in an emotional rather than a neutral context.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is entirely consistent with the results of studies of long-term memory for emotional events, which have shown that emotions improve the memories of events and of some of their properties (e.g., location) (e.g., D'Argembeau & Van der Linden, 2004;Dunbar & Lishman, 1984). Therefore, contrary to findings in the literature on time distortions in long-term memory for emotional events, our results suggest that durations are remembered better when they are initially experienced in an emotional rather than a neutral context.…”
Section: Discussionsupporting
confidence: 81%
“…Bradley, Mogg & Williams, 1995;Dunbar & Lishman, 1984;Watkins, Mathews, Williamson & Fuller, 1992). In contrast there has been relatively little investigation of the effect of depression on memory for nonverbal emotional cues, notably emotional faces.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kindermann and Brown found a bimodal distribution of memory deficits, in their sample of studies, which was attributed mainly to patient characteristics such as depressive subtype and age. It should be noted that a number of individual studies focusing on neurologically unimpaired individuals with major depressive disorder have resulted in equivocal findings regarding the negative effects of depression on memory (Dunbar & Lishman, 1984;Newman & Sweet, 1986;Williams, Iacono, Remick, & Greenwood, 1990). Despite the apparent consistency among meta-analyses, there does appear to be substantial variability within depressed groups.…”
mentioning
confidence: 99%